2005
DOI: 10.1111/j.1365-2036.2005.02339.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of esomeprazole 40 mg vs. lansoprazole 30 mg for healing moderate to severe erosive oesophagitis

Abstract: Summary Background : Secondary analyses from previous studies indicated that esomeprazole was more effective than lansoprazole and omeprazole in healing moderate or severe (Los Angeles grades C or D) erosive oesophagitis (EE). Aim : To compare prospectively healing rates with esomeprazole vs. lansoprazole in patients with moderate to severe EE. Methods : In this multicentre, randomized, double‐blind, parallel‐group trial, adult patients with endoscopically confirmed moderate or severe EE received esomeprazole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 23 publications
0
71
0
Order By: Relevance
“…19,20 The primary objective of this study was to compare the effects of once and twice daily dosing of esomeprazole 40 mg and lansoprazole 30 mg on intragastric pH over a 24-hour period in patients with GERD symptoms. This study uses a novel crossover design to evaluate the effects of once and twice daily dosing of two different PPIs.…”
mentioning
confidence: 99%
“…19,20 The primary objective of this study was to compare the effects of once and twice daily dosing of esomeprazole 40 mg and lansoprazole 30 mg on intragastric pH over a 24-hour period in patients with GERD symptoms. This study uses a novel crossover design to evaluate the effects of once and twice daily dosing of two different PPIs.…”
mentioning
confidence: 99%
“…Two of the three studies compared the healing efficacy of esomeprazole 40 mg with lansoprazole 30 mg (capsules containing 30 mg of active ingredient) (11,12,19). Of these two studies, one included patients with RE of Los Angeles (LA) classification grade A-D (11,19), while the other included only patients with more severe RE, i.e.…”
Section: Healing Studiesmentioning
confidence: 99%
“…Three studies evaluating healing of RE after 4-8 weeks of once-daily treatment with esomeprazole 40 mg (esomeprazole magnesium trihydrate 44.5 mg) or a comparator PPI were included (11,12,15,19). In all studies, the primary efficacy end-point was endoscopically-confirmed RE healing at week 8.…”
Section: Healing Studiesmentioning
confidence: 99%
See 2 more Smart Citations